2007
DOI: 10.1111/j.1502-3885.2007.tb01249.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution stratigraphy of the northernmost concentric raised bog in Europe: Sellevollmyra, Andøya, northern Norway

Abstract: From the Sellevollmyra bog at Andøya, northern Norway, a 440‐cm long peat core covering the last c. 7000 calendar years was examined for humification, loss‐on‐ignition, microfossils, macrofossils and tephra. The age model was based on a Bayesian wiggle‐match of 35 14C dates and two historically anchored tephra layers. Based on changes in lithology and biostratigraphical climate proxies, several climatic changes were identified (periods of the most fundamental changes in italics): 6410–6380, 6230–6050, 5730–564… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 73 publications
(97 reference statements)
2
48
0
Order By: Relevance
“…Hall and Pilcher, 2002). According to proximal deposits, however, the main transport component of this eruption was to the north and northeast (Thorarinsson, 1967;Larsen et al, 1999), yet Hekla-1 has only been identified in two distal sites in northern Norway and within marine records off the Icelandic coast (Larsen et al, 2002;Pilcher et al, 2005;Kristjansdó ttir et al, 2007;Vorren et al, 2007). This may be a feature of where tephra investigations over the last 1000 a have been conducted in recent years rather than a real absence of Hekla-1 tephra.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Hall and Pilcher, 2002). According to proximal deposits, however, the main transport component of this eruption was to the north and northeast (Thorarinsson, 1967;Larsen et al, 1999), yet Hekla-1 has only been identified in two distal sites in northern Norway and within marine records off the Icelandic coast (Larsen et al, 2002;Pilcher et al, 2005;Kristjansdó ttir et al, 2007;Vorren et al, 2007). This may be a feature of where tephra investigations over the last 1000 a have been conducted in recent years rather than a real absence of Hekla-1 tephra.…”
Section: Discussionmentioning
confidence: 92%
“…Hekla-1 is one of the most widespread Holocene tephras from Iceland and was reported in Scandinavian peat bogs as early as the 1960s (Persson, 1966). Persson's records were not confirmed by geochemical analyses, however, and it was not until recently that the Hekla-1 was securely identified in sequences in Scandinavia (Pilcher et al, 2005;Vorren et al, 2007). This tephra is also the most reported historic tephra in Ireland (Pilcher et al, 1996;Hall and Pilcher, 2002;Chambers et al, 2004), and has been used to constrain timeframes for climate and human impact studies of Irish bogs (Hall, 2003;Hall and Mauquoy, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations